Ratholen : Ein Kunstprojekt der Stadt Dachau. - Schürholz, Marietta; Bürgel, Peter; Stanic, Michael (Bonn : VG Bild-Kunst, 2002)
Bachmayer, Vinzenz ; Beuys, Joseph ; Blum, Heiner ; Eickhoff, Hayo ; Heinert, Jürgen ; Musierowicz, Piotr ; Ohmayer, Andreas ; Pittroff, Susanne ; Polonyi, Carl ; Röder, Tanja et al.
boek